The “reverse” Code Green: Stories of mass evacuation of correctional centres - Christensen, Lorna C. J.; Egli, Shelly L. (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence)

(untitled) (Meadowlight Media, 2026)
Emergency preparedness is essential, especially given global climate change (World Health Organization, 2023, para. 1). Healthcare systems have formal plans for different types of disasters and emergencies so that when a disaster occurs, there is an outlined course of action. In most healthcare settings in Canada, a Code Green is called for an evacuation, and a Code Orange is called for a mass casualty event. Correctional health—a unique and often overlooked area in healthcare—is not immune to disaster events, and there is a considerable lack of literature specific to disasters and correctional health services. Over the last 2 years, our correctional centre has been the receiving site for two mass evacuations, both secondary to a natural disaster. In this article, we discuss lessons learned at our facility from these external disaster events, and summarize what we can do in future, including what might be helpful for other correctional and hospital sites. Some themes and mitigation strategies identified were moving clients, getting information, gathering supplies, and leading teams. We include a brief discussion of electronic health records and creative staffing strategies. Our biggest lesson was in the importance of planning ahead, and so it would be prudent for all correctional sites around the globe to consider what resources they have available to them if they were to send or receive a high volume of clients due to evacuation.